Modern Conversion Layers as High-Performance Alternatives to Aluminum Anodizing and Its Alloys - Chvojka, Martin; Kreibich, Viktor; Kudláček, Jan (Manufacturing Technology Journal, 2024)
The paper focuses on a novel and perspective surface treatment technology called Plasma Electrolytic Oxidation (PEO) applied to aluminium and its alloys. This innovative technology generates layers with specific properties, particularly suitable for tribological and heat-resistant applications. Plasma Electro-lytic Oxidation technology represents an alternative to conventional oxidation methods, offering high utility properties and presenting a completely new approach to surface modification.
Keywords: PEO (Plasma Electrolytic Oxidation); Non-ferrous Metal Anodizing; Conversion Layers; Conventional Anodization